Firms' Choice of R&D Intensity in the Presence of Aggregate Increasing Returns to Scale - Stefan Fölster (The Research Institute of Industrial Economics (IUI), 1989)
When firms possess unique R & D assets such as ideas or particular researchers, and there are aggregate increasing returns to scale in R & D, then there can be several Nash equilibria involving different levels of investment in R & D. However when costless communication is possible firms may be able to coordinate a move towards a pareto-preferred equilibrium provided that the communication is credible. It is shown that in some cases when firms do not move to a pareto-preferred equilibrium in spite of communication one firm may have an incentive to purchase R & D assets from other firms to reap the gain from moving to a high R & D-intensity equilibrium. In the absence of common knowledge however it is not clear whether players will choose strategies that lead to Nash equilibria. Two hypotheses in this case are that communication is much less useful and that the concentration of R & D assets influences players entry decision. These hypotheses are confirmed in a laboratory experiment.
Keywords: D83; O32; 330; R&D; Nash equilibria; coordination; Pareto-preferred outcome; communication